Noncalcified Plaque in Cardiac CT: Quantification and Clinical Implications - Hell, Michaela; Achenbach, Stephan; Shah, Prediman K.; Berman, Daniel S.; Dey, Damini (Current Cardiovascular Imaging Reports, 2015)
Coronary computed tomography angiography (CTA) is being increasingly used for direct, noninvasive evaluation of the coronary arteries. Beyond stenosis, coronary CTA also permits assessment of atherosclerotic plaque (including total and noncalcified plaque burden) and coronary artery remodeling, previously only measurable through invasive techniques. It has been shown that coronary plaque volume for noncalcified and mixed plaques and the arterial remodeling index correlate closely with corresponding measures from invasive intravascular ultrasound. Several studies have also shown a strong relationship between adverse plaque features imaged by coronary CTA and acute coronary syndrome, major adverse cardiovascular events, and ischemia. The aim of this review is to summarize current methods for quantitative measurement of atherosclerotic plaque features from coronary CTA and to discuss the clinical implications of noncalcified plaque as detected by CTA and reported in the current literature.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Coronary artery plaque; Coronary computed tomography angiography; Noncalcified plaque; Plaque characterization; Plaque quantification